MENINGKATKAN MINAT BELAJAR MENGAJI ANAK USIA DINI - Indah Irawati; Kesuma Putri (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2021)
The level of interest in learning the Koran in today's era has greatly decreased both among adults and early childhood. With the development of technology today, people prefer online learning systems such as watching YouTube, Google, and using the Digital Qur'an instead of having to study with an ustadz or a Koran teacher.Learning to recite the Koran is something that we should develop and start from an early age so we don't regret it in old age. Where, if we look at it today, many adults, both teenagers and parents, are illiterate.Improving interest in learning the Koran for more effective early childhood should be done by learning directly from the teacher reading the Koran. Why should this be done? So that children can interact directly and understand more and be more responsive to recognizing hijaiyah letters or verses of the Qur'an. Apart from this, parents at home must also invite children to repeat the lessons that have been taught by the Koran teacher as a form of support from parents for the child himself.It is important for them in the future, because reciting the Qur'an is a worship where if you do it you will get a reward. Al-Qur'an is the way of life for Muslims, therefore we must study it and understand its contents.